Correction to: Electrochemical and physiochemical studies on the effects of thiadiazole derivatives in corrosion inhibition of Muntz metal in sulfide-polluted marine environment (Journal of Applied Electrochemistry, (2024), 54, 5, (1203-1221), 10.1007/s10800-023-02009-4) - Ravisankar P.; Murugasamy J.; Ayyaru S.; Kanagaraj S.; Alagarasan J.K.; Hasan I.; Somu P.; Yadav A.K.; Ahn Y.-H. (My University, 2025)
In the original publication of the article, the author's information in the supplementary information file was published incorrectly. The updated supplementary information file with the correct author's information and the affiliation details are provided in this correction. The original article has been corrected. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.